The Problem and Solutions of Tahfidz Qur’an Learning at Nur Hidayah Integrated Islamic Senior High School Kartasura - Al Ayubi, Avid; Chusniatun, Chusniatun (Journal of Educational Sciences, 2025)
The learning of Tahfidz Qur'an plays a crucial role in preserving the purity and authenticity of the Qur'an. This study aims to analyze the challenges and formulate solutions in the Tahfidz Qur'an learning process at Nur Hidayah Integrated Islamic Senior High School (SMAIT) Kartasura. The research method used is qualitative with a phenomenological approach, where data is collected through observations, interviews with instructors and students, and documentation studies. The results show that the Tahfidz learning process still faces various obstacles, such as low student motivation, lack of discipline in memorization, boredom due to monotonous teaching methods, limited time for memorization submission, and an insufficient number of instructors. To overcome these challenges, the school implements several strategies, including special assistance for students experiencing difficulties, a group rotation system for memorization, rewards for outstanding students, and training for instructors to improve teaching quality. Additionally, Tahfidz quarantine programs and annual evaluations are applied to maximize students’ memorization achievements. By implementing these strategies, the Tahfidz Qur'an learning process at the school is expected to become more effective, sustainable, and produce students with better and higher-quality memorization.